(untitled) (Journal of Asian Development Studies, 2025)
The increasing prevalence of social media use has raised concerns about its potential effects on university students’ psychological experiences and academic outcomes. Although previous research has examined social media addiction, fear of missing out (FoMO), and academic performance, cross-cultural evidence comparing students from Pakistan and the United States of America remains limited. The present study aimed to investigate the relationships among social media addiction, FoMO, and academic performance and to examine cross-cultural differences between university students in the two countries. A cross-cultural, cross-sectional correlational design was employed, and data were collected from 200 university students (Pakistan = 100; United States = 100) aged 18–35 years using purposive sampling. Standardized measures of social media addiction, FoMO, and academic performance were administered. Correlation analyses indicated a strong positive association between social media addiction and FoMO, while both variables showed significant negative relationships with academic performance. Independent sample t-tests revealed no significant differences between Pakistani and U.S. students in social media addiction or FoMO. However, Pakistani students reported significantly higher academic performance than their U.S. counterparts. These results underscore the importance of culturally informed strategies to promote balanced social media use and academic success among students.